Synchronisation of tibial rotational alignment with femoral component in total knee arthroplasty - Lee, Dong-Hoon (Springer-Verlag, 2007)
The rotational axis of the tibial component in total knee arthroplasty described by Insall is generally accepted, but rotational mismatch between the femoral and the tibial components can occur because the alignment of each component is determined separately. We developed a connecting instrument to synchronise the axis of the tibia to the axis of the femur. We compared the rotational axis of the tibial component using our method and medial one third of tibial tuberosity (Insall’s reference) in 70 consecutive TKAs. The rotational axis of the tibial component from the femoro-tibial synchronisation was rotated internally 13.8° ± 5.8° (range, 2° – 24°) more than the axis of Insall’s reference. Eighty three percent of patellae tracked centrally and the patellae tilt measured 2.2° on average. More attention should be given to the rotational congruency between the femoro-tibial components, because the recent prosthetic design has more conforming articular surfaces.